“Status,” Inter-Normativity, and Socio-Professional Differentiation among Construction Workers in Douala, Cameroon - Ludovic Bakebek (Africa Spectrum)
Based on qualitative research conducted in the construction sector in Douala, Cameroon, this article analyses the contractual practices that underpin employment relationships between construction actors. The aim is to provide an account of the social dynamics that lead to the differentiation of employment conditions in the construction sector beyond the binary categorisations that set formal against informal in analyses of African labour markets. The central argument here is that, beyond formality, the relationship between stability/protection and uncertainty/precariousness is based on the category of status, defined as the “perceived quality” of workers. Employment relationships based on status are organised through interrelated legal, social, and moral norms (inter-normativity) that contribute to differentiating socio-professional experiences. This is illustrated through a series of case studies, ranging from the salaried segment of the construction sector to the large market of auto-construction dominated by micro-entrepreneurs.